Empowering Agricultural Economic Resilience in China: Does Green Finance Matter? - Xin Zhong; Jian Wang (Advances in Agriculture)
This study employs provincial panel data from China spanning 2012–2021, utilising the entropy weight method and spatial Durbin model to analyse agricultural economic resilience through the lens of green finance. Key findings reveal: (1) National resilience levels are rising steadily, with a shift from the Eastern Region to the Central Region. (2) Green finance (GF) development displays an initial decline followed by an upward trend, mirroring resilience trends. (3) GF positively impacts resilience, with a 0.0325% increase for every 1% GF rise. (4) GF exhibits a significant positive spatial spillover effect, enhancing surrounding regions’ resilience by 0.3098% per 1% GF increase. (5) GF’s influence on resilience differs regionally, stronger in the East than the Central and West. We propose strategies to enhance rural GF systems, energy-efficient innovations and regulatory frameworks to foster regional cooperation and ultimately bolster resilience. This research offers valuable insights for developing nations.